Kadar imunoglobulin A sekretori pada penderita tonsilitis kronik sebelum dan setelah tonsilektomi - Indo Sakka; Raden Sedjawidada; Linda Kodrat; Sutji Pratiwi Rahardjo (Oto Rhino Laryngologica Indonesiana, 2011)
Background: Infection of the tonsils is a fairly common problem in the population. The complaints among others are pain while swallowing, fever, otitis media, until obstructive sleep apnea. Until now tonsillectomy procedure is still a controversy. For those against it, tonsillectomy is considered decreasing the body’s defense mechanism. Purpose: The goal of the research is to analyze the secretory immunoglobulin A level on the chronic tonsillitis patients before and after tonsillectomy.Method: The research was conducted as a comparative analytic study among the chronic tonsillitis patients before  and after tonsillectomy. Result: The result of this study reveals that the level of secretory Ig A in healthy  subjects were 5358.2200 + 1071.23 ng/ml, in chronic tonsillitis patients before tonsillectomy were 7539.6563 + 2293.07 ng/ml, and after tonsillectomy were 5946.4375 + 2133.13 ng/ml. Conclusion:  The level of s-IgA in chronic tonsillitis prior to tonsillectomy was high and 4 weeks post operation the level of s-IgA decreased, close to the level of normal subjects. Keywords: secretory immunoglobulin A, chronic tonsillitis, tonsillectomy Abstrak :  Latar belakang: Infeksi pada tonsil merupakan masalah yang cukup sering dijumpai. Keluhan yang ditimbulkan berupa nyeri menelan, demam, otitis media, sampai obstructive sleep apnea. Sampai saat ini tonsilektomi masih menimbulkan kontroversi. Bagi yang kontra, tonsilektomi dianggap dapat menurunkan sistem pertahanan tubuh. Tujuan: Mengetahui kadar Imunoglobulin A sekretori (s-IgA) pada penderita tonsilitis kronik sebelum dan setelah tonsilektomi. Metode: Analitik komparatif yang dilakukan pada penderita tonsillitis kronik sebelum dan setelah tonsilektomi. Hasil:Kadar s-IgA individu sehat adalah 5358.2200 + 1071.23 ng/ml, s-IgA penderita tonsilitis kronik sebelum tonsilektomi adalah 7539.6563 + 2293.07 ng/ml, sedangkan s-IgA penderita tonsilitis kronik setelah tonsilektomi adalah 5946.4375 + 2133.13 ng/ml. Kesimpulan: s-IgA penderita tonsilitis kronik sebelum tonsilektomi kadarnya tinggi. Empat minggu setelah operasi, kadar s-IgA turun mendekati kadar s-IgA individu normal. Kata kunci: imunoglobulin A sekretori, tonsillitis kronik, tonsilektomi